DAMPAK POSITIF DAN NEGATIF SOSIAL MEDIA TERHADAP PENDIDIKAN AKHLAK ANAK (Studi Kasus di SMP Negeri 2 Kelas VIII Banda Aceh) - Nisa Khairuni (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2016)
The author examines the positive and negative effects of social media on the moral education of children in school SMPN 2 class VIII Banda Aceh, it is very interesting because of the many children who abuse social media. This work analyzes about the use of social media that have an impact on the moral education of children. The data collected in this study through the work of other literature, researchers also interviewed principals and students as many as 16 students as well as the observation at the school. Based on the analysis that has been done it can be seen the positive and negative impacts of the use of social media to the moral education of children. The positive impact on the social development of the media on moral education of children among children can adapt, socialize with the public and manage a network of friends, and make children easier to accomplish these tasks, while the negative impact of the development of social media to the moral education of children very much of them can make the omission in children so that children are less disciplined and be lazy, makes children easy to cheat the works of others, disrespectful both in dress and speech, often quarrel due to scenes that are as dangerous as scenes of pornography, violence, wars and so forth , as well as making children miss school because they feel more comfortable in the cafe of the study at the school, not only that social media also makes children spend pocket money a child so that the child took the money her parents secretly to access the internet cafe. Therefore, social media can lead education of children.